Studies on cross compatibility in Dendrobium species and hybrids - Devadas, R.; Pattanayak, S.L.; Singh, D.R. (The Indian Journal of Genetics and Plant Breeding, 2016)
Gene pool of Dendrobium species from Eastern Himalayan region is largely unexploited in India. Cross compatability was studied in 23 species and 14 hybrids of Dendrobium for two consecutive years, based on synchrony of flowering. The success of pod setting in species vs species was recorded limiting to 8.97% in direct crosses and 18.75% in respective possible reciprocal crosses. However, 34.37% pod formation was observed in direct crosses in species vs hybrids vs hybrids combinations and 50% success in their reciprocal crosses. Among the species, cane orchid (Dendrobium moschatum) is compatible as both male and female parents, apart from hybrids ‘Emma White’ and ‘Thongchai Gold’. Twelve species failed to get pod formation as both male and female parents that belong to section-II of Eugenanthe (Dendrobium), Callista and Aporum that are native to Eastern Himalayan region. The larger group of Indian Dendrobium species that grouped in Dendrobium section was found to be incompatible with other sections and the success of intra-sectional combinations was limited to only 5.8 %. However, species from sections Callista followed by Eugenanthe and Dendrobium were cross compatible with hybrids with 85.7 %, 40 % and 33.3 % success of pod formation, respectively. These findings suggest intermediary approaches to develop bridge crosses to overcome incompatibility barriers in Dendrobium improvement programmes.